2016
DOI: 10.1002/jsfa.7991
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of grape pomace from red wine by-product as feed for sheep

Abstract: The nutritive value of grape pomace varies depending on the proportion of seeds and pulp. The interest of this by-product in sheep feeding could be related to its polyphenol and PUFA content, which could improve meat and milk quality. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…As said, grape marc is one of the most abundant by-products of wine industry being in winemaking countries such as Spain around 1200 t per year (Beres et al 2017). Grape marc can also be considered a low-cost source of polyphenols, which could have interesting applications in many different industries (Guerra-Rivas et al 2017;Mattos et al 2017;González-Centeno et al 2013) along with its upgrading to become a high valuable by-product (Yammine et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As said, grape marc is one of the most abundant by-products of wine industry being in winemaking countries such as Spain around 1200 t per year (Beres et al 2017). Grape marc can also be considered a low-cost source of polyphenols, which could have interesting applications in many different industries (Guerra-Rivas et al 2017;Mattos et al 2017;González-Centeno et al 2013) along with its upgrading to become a high valuable by-product (Yammine et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, both values were within the recommended range of 361-556.5 Kilojoules (KJ) metabolizable energy (ME)/kg of metabolic live-weight required for maintenance of ruminants [18]. The lignin content in grape pomace is higher than that in citrus pulp ( Table 1) and is above the 40 g/kg DM suggested as the threshold level at which DM intake and digestibility in ruminants could be depressed [19]. The calcium, phosphorus, and magnesium content of citrus pulp and grape pomace are within the recommended maintenance requirements for ruminants of 15.4 mg Ca/kg, 16 mg P/kg, and 12-16 mg Mg/kg body weight, respectively [18].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, suckling lambs, whose mother's diets were supplemented with 5% or 10% of grape pomace, had greater proportion of vaccenic, rumenic acids, and n-3 : n-6 ratio, but a lower oleic acid percentage in their intramuscular fat compared to a control diet [34]. This effect was thought to be related to the contribution of linoleic acid and the inhibitory effect of some phenolic compounds present in the wine by-product on ruminal biohydrogenation [24,35]. However, a fourth treatment used in the same study, with 500 mg kg −1 of -tocopherol added, showed similar results than the grape pomace treatments (with no contribution of further fatty acids and phenolic compounds) [34].…”
Section: Meat Fatty Acid Compositionmentioning
confidence: 99%